2017
DOI: 10.1038/s41598-017-11135-x
|View full text |Cite
|
Sign up to set email alerts
|

Channel Formation and Membrane Deformation via Sterol-Aided Polymorphism of Amphidinol 3

Abstract: Amphidinol 3 (AM3) is an anti-fungal polyene extracted from a marine dinoflagellate. Here, we examined the ion channel activity and membrane-embedded structure of AM3 using a lipid bilayer method and atomic force microscopy (AFM). AM3 exhibited large-conductance (~1 nS) and non-selective single-channel activity only when sterols were present in the membrane leaflet of the AM3-added side. The variable conductance suggests the formation of a multimeric barrel-stave pore. At high AM3 concentrations, giant-conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 44 publications
(49 reference statements)
0
20
0
Order By: Relevance
“…The wide range of techniques that have been used to measure AMPs activity (i.e., fluorescence resonance energy transfer (FRET), small angle neutron scattering (SANS), nuclear magnetic resonance (NMR), calorimetry, electrophysiology, X-Ray, or circular dichroism (CD)) provide little information on the oligomerization states which is an important piece of information missing in our understanding of the activity of the peptides 29 ; as oligomerization controls the nature, dynamics and regularity of the membrane deformations. Atomic force microscope (AFM) and electrochemical scanning tunnelling microscopy (EC-STM) are unique in their capability of label-free high resolution imaging of biological molecules and their surroundings under physiological conditions, yet, in the literature, few studies address the effect of AMPs on supported lipid bilayers by AFM [32][33][34][35][36][37][38][39][40][41][42][43][44] (Dap in particular was never studied), most are prior to 2011, few are the recent publications [42][43][44] . The published AFM data examines the evolution of the contours of membranes patches exposed to AMPs in solution.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The wide range of techniques that have been used to measure AMPs activity (i.e., fluorescence resonance energy transfer (FRET), small angle neutron scattering (SANS), nuclear magnetic resonance (NMR), calorimetry, electrophysiology, X-Ray, or circular dichroism (CD)) provide little information on the oligomerization states which is an important piece of information missing in our understanding of the activity of the peptides 29 ; as oligomerization controls the nature, dynamics and regularity of the membrane deformations. Atomic force microscope (AFM) and electrochemical scanning tunnelling microscopy (EC-STM) are unique in their capability of label-free high resolution imaging of biological molecules and their surroundings under physiological conditions, yet, in the literature, few studies address the effect of AMPs on supported lipid bilayers by AFM [32][33][34][35][36][37][38][39][40][41][42][43][44] (Dap in particular was never studied), most are prior to 2011, few are the recent publications [42][43][44] . The published AFM data examines the evolution of the contours of membranes patches exposed to AMPs in solution.…”
mentioning
confidence: 99%
“…Never have the dynamics of the activity of AMPs been imaged at molecular resolution, for example oligomers could never be visualised due to their thermal diffusive motion. AFM and EC-STM molecular imaging was restricted to the static final states of the processes 32,39,42,43 , hence, overlooking the core of the AMPs molecular activity. Overall, the incapability to assert AMPs molecular activity hampers the straightforward correlation of the AFM data with the molecular, but averaged, information issued from the prevalent techniques of monitoring of AMPs molecular activity 36 .…”
mentioning
confidence: 99%
“…5 ), suggesting that AM3 more effectively enhances the order of the disordered membrane than that of ordered membrane. It is reported that AM3 forms domain-like aggregate on the membrane [ 18 ], which may increase the membrane order.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous study using surface plasmon resonance (SPR) and solid-state 2 H NMR demonstrated that AM3 directly interacts with sterols in membranes [ 17 ]. In addition, more recent channel recording experiments further suggest that AM3 forms both barrel-stave and toroidal pores depending on the AM3 concentration; a higher concentration of AM3 forms jumbo toroidal pores, while a lower concentration of AM3 forms a barrel-stave channel that shows a single channel property [ 18 ].
Fig.
…”
Section: Introductionmentioning
confidence: 99%
“…Membrane manipulation is not limited to physical and chemical procedures conducted on the bilayer itself, but now include alterations to membrane-incorporated channels, such as channel forming substances, which may deform the membrane upon channel formation. [80][81][82] Our picture of channel-membrane interplay is more and more realistic through touching the membrane and designing more sophisticated membranes.…”
Section: Conclusion: Channel-membrane Inter-playmentioning
confidence: 99%